1999
DOI: 10.1006/viro.1999.9974
|View full text |Cite
|
Sign up to set email alerts
|

The FeLV-945 LTR Confers a Replicative Advantage Dependent on the Presence of a Tandem Triplication

Abstract: Feline leukemia virus (FeLV), like other naturally occurring retroviruses, is characterized by a high degree of genetic diversity. FeLV-945 is a natural isolate derived from non-B-cell non-T-cell lymphomas classified anatomically as multicentric. FeLV-945 exhibits a unique structural motif in the LTR composed of a 21-bp tandem triplication downstream of a single copy of enhancer. The unique FeLV-945 LTR is precisely conserved among eight independent multicentric lymphomas collected in a geographic cluster. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 38 publications
(71 reference statements)
2
41
0
1
Order By: Relevance
“…Regarding the mechanism by which the FeLV-945 LTR confers a replicative advantage, our studies identified binding sites for the transcription factor, c-Myb, that cross the repeat junctions of the 21-bp triplication (Prabhu et al, 1999;Finstad et al, 2004). It was intriguing to identify binding sites that cross the repeat junctions, because such sites would not occur in the absence of the repeat; thus, a requirement for c-Myb binding to the repeat junctions of the triplication might represent a selective pressure to conserve its sequence precisely.…”
Section: Predominance Of Felv-945 Ltr Reflects Replicative Fitnessmentioning
confidence: 96%
See 4 more Smart Citations
“…Regarding the mechanism by which the FeLV-945 LTR confers a replicative advantage, our studies identified binding sites for the transcription factor, c-Myb, that cross the repeat junctions of the 21-bp triplication (Prabhu et al, 1999;Finstad et al, 2004). It was intriguing to identify binding sites that cross the repeat junctions, because such sites would not occur in the absence of the repeat; thus, a requirement for c-Myb binding to the repeat junctions of the triplication might represent a selective pressure to conserve its sequence precisely.…”
Section: Predominance Of Felv-945 Ltr Reflects Replicative Fitnessmentioning
confidence: 96%
“…FeLV LTR sequence variation in the cohort was examined using PCR amplification and nucleotide sequence analysis. Specifically, genomic DNA from diseased tissues was amplified by PCR using primers specific for the U3 region of exogenous FeLV LTR (Prabhu et al, 1999;Chandhasin et al, 2004). Amplification products of multiple sizes were detected from most animals, indicating the presence of FeLV LTR sequence variation within the tissues of individuals.…”
Section: The Unique Felv-945 Ltr Predominates In Non-t-cell Diseases mentioning
confidence: 99%
See 3 more Smart Citations